Performance and Protein Efficiency Ratio of Starter Phase Pegagan Ducks Fed Fermented Rations Made from Locally Sourced Materials - Sandi, Sofia; Yosi, Fitra; Miksusanti (Pakistan Journal of Nutrition, 2016)
This study examined locally sourced raw materials that were either fermented or not with different inoculums to determine the effect of diet on performance and protein efficiency ratio in young Pegagan ducks. A completely randomized design (CRD) with 5 treatments and 4 replications was used to examine five rations: R0, commercial ration (control), R1; locally sourced ration without fermentation; R2, locally sourced ration fermented with bread yeast; R3, locally sourced ration fermented with tape yeast and R4, locally sourced ration fermented with tempeh yeast. Variables measured were final body weight, feed intake, weight gain, feed conversion, protein intake, protein digestibility, protein degradation and protein efficiency ratio. Data were analyzed with ANOVA and Duncan’s multiple range test. The use of locally sourced raw material feed fermented using different inoculums had significantly difference (p<0.05) on the final body weight, weight gain, feed conversion, protein digestibility, protein degradation and protein efficiency ratio, but did not have significantly difference (p>0.05) on feed and protein intake of Pegagan ducks. It was concluded that the use of local raw material feed fermented with different inoculums had the same result on increase the final body weight, body weight gain, feed conversion, protein digestibility, protein degradation and protein efficiency ratio in Pegagan ducks.